MANAJEMEN PEMBIAYAAN PRAKTEK KERJA INDUSTRI - Mirsalin Mirsalin Mirsalin (UNIVERSITAS BENGKULU, 2016)
The purpose of this study is to describe the financial planning, how to obtain the cost, implementation and evaluation of the cost of the Industrial Work Paractice at the Vocational HighSchool Number 2 of Bengkulu. This research is descriptive qualitative. The technique of collecting data using interview, observation and documentation study. Analysis of the data through the stages: data reduction, data presentation, comparing the data, conclusion. Results of this study are:(1) The financial planning include: setting of goals, programs, procedures, and budget; (2) financing only comes from government of Bengkulu City; (3) implementation includespreparation, committees, working together, monitoring, activity report; (4) evaluation includes financial administration, and accountability reports.Keywords: management, finance, industrial work practice